Sosialiasasi Kecacingan pada Anak di Desa Taman Ayu, Kabupaten Lombok Barat - Adelia Riezka Rahim; Eva Triani; Putu Suwita Sari (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Parasitic worm infections remain a significant health burden for children in West Lombok, particularly in Taman Ayu Village, which has high environmental and behavioral risk factors. The socialization activity at SDN 1 Taman Ayu successfully engaged parents, guardians, and students to emphasize the medical risks associated with worm infections and the importance of disease prevention. By educating children and parents/guardians about the risk factors and prevention strategies of worm infections, this program is expected to raise community awareness of the issue. This initiative highlights the crucial role of health education in reducing the prevalence of worm infections and promoting healthier growth and development among elementary school-aged children.